Incidence of G6pd Deficiency in Young Asymptomatic Males in Pakistan - Hania Afzal, Aamir Hussain, Sqn Ldr Shujee Ahmad, Umer Bin Tariq, Baseera Imran, Abdul Karim Soomro, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: NADPH is crucial for glutathione reduction. Deficiecy of G6PD leads to excessive oxidised glutathione that denatures hemoglobin and forms Heinz bodies. Heinz bodies damages RBC membrane and cause premature removal of cells by spleen. G6PD deficiency is the most common X-linked inherited red cell enzymopathy that leads to hemolytic anemia and neonatal jaundice in enzyme deficient patients under oxidative stress. G6PD is the rate limiting enzyme in pentose phosphate pathway, a dominant form of glycolysis in RBCs. G6PD converts glucose-6 phosphate into 6-phosphonogluconolactone and reduces NADP to NADPH. Objective: To determine incidence of G6PD deficiency in young healthy males in Pakistan. Study design: A descriptive cross sectional study Place and duration: Study was carried out at PAF Hospital Sargodha from Jan 2021 to Feb 2023 Methodology: G6PD levels were checked in young healthy male volunteers of 12 to 18 years of age, after taking informed consent from subjects and their parents. Results: Out of 1493 volunteers, only 61 were G6PD deficient and rest all had normal levels. This shows an incidence of 4.08% in our population. Conclusion: Comparing with previous studies suggests 2-4% incidence of G6PD deficiency in Pakistani population. A larger study including females and studying variants of disease is needed. Patients with lab confirmed P.Vivax should get screened for G6PD deficiency, so that they receive Primaquine. Keywords: Incidence, G6PD deficiency, Malaria, Primaquine.